The Socialization Of Patriotism In Jagoi Babang Sub-District - Zulfahita Zulfahita; Citra Utami; Fajar Wulandari; Fitri Fitri; Iip Istirahayu (International Journal of Public Devotion, 2019)
Indonesia is a country that has a variety of cultures, ethnicities, and races. This diversity is characteristic of the Indonesian state and the assets of the Indonesian people, in accordance with the motto of Unity in Diversity. Therefore, it is important for every citizen to have a sense of patriotism as a form of pride in the country of birth and shelter. The love of the motherland is not only implemented in the world of education, but also must be in the community, one of which is by conducting socialization to the community about the importance of the love of the motherland and then proceed with the screening of the Indonesian film titled "Merah Putih Memanggil (Red and White Calling)". This activity was carried out on Thursday, January 17, 2019, located in Jagoi Village, Jagoi Babang District. Participants in this activity were children and residents of Jagoi village and several members of the TNI from the Task Force Yonif 511 / DY. Through these activities, the aim is to further instill a sense of patriotism for participants who basically reside in the border area, namely the village of Jagoi, Jagoi Babang.